Extracellular histones are a target in myocardial ischaemia–reperfusion injury. Issue 4 (20th April 2021) - Shah, Mohammed; He, Zhenhe; Rauf, Ali; Beikoghli Kalkhoran, Siavash; Heiestad, Christina Mathisen; Stensløkken, Kåre-Olav; Parish, Christopher R; Soehnlein, Oliver; Arjun, Sapna; Davidson, Sean M; Yellon, Derek
Abstract: Aims : Acute myocardial infarction causes lethal cardiomyocyte injury during ischaemia and reperfusion (I/R). Histones have been described as important Danger Associated Molecular Proteins (DAMPs) in sepsis. The objective of this study was to establish whether extracellular histone release contributes to myocardial infarction. Methods and results : Isolated, perfused rat hearts were subject to I/R. Nucleosomes and histone-H4 release was detected early during reperfusion. Sodium-β-O-Methyl cellobioside sulfate (mCBS), a newly developed histone-neutralizing compound, significantly reduced infarct size whilst also reducing the detectable levels of histones. Histones were directly toxic to primary adult rat cardiomyocytes in vitro. This was prevented by mCBS or HIPe, a recently described, histone-H4 neutralizing peptide, but not by an inhibitor of TLR4, a receptor previously reported to be involved in DAMP-mediated cytotoxicity. Furthermore, TLR4-reporter HEK293 cells revealed that cytotoxicity of histone H4 was independent of TLR4 and NF-κB. In an in vivo rat model of I/R, HIPe significantly reduced infarct size. Conclusion : Histones released from the myocardium are cytotoxic to cardiomyocytes, via a TLR4-independent mechanism. The targeting of extracellular histones provides a novel opportunity to limit cardiomyocyte death during I/R injury of the myocardium. Graphical Abstract: